Impact of polyphenols in phagocyte functions - da Cunha LR; Muniz-Junqueira MI; dos Santos Borges TK (Dove Medical Press, 2019)
Leandro Rodrigues da Cunha, Maria Imaculada Muniz-Junqueira, Tatiana Karla dos Santos BorgesLaboratory of Cellular Immunology, Pathology, Faculty of Medicine, University of Brasilia, Brasília, BrazilCorrespondence: Tatiana Karla dos Santos BorgesLaboratory of Cellular Immunology, Pathology, Faculty of Medicine, University of Brasilia, Campus Darcy Ribeiro, Brasilia, Distrito Federal 70.910.900, BrazilEmail tatianakarlab@gmail.comAbstract: Polyphenols are a broad group of substances with potential health benefits found in plant species. Several of these compounds are capable of influencing the activation of intracellular signaling pathways, such as NF-kB, MAPK and JAK-STAT, responsible for the production of various inflammatory mediators such as tumor necrosis factor α (TNF-α) and interleukin 1 beta (IL-1β) and 12 (IL-12), enzymes involved in the production of reactive species such as inducible nitric oxide synthase (iNOS) and superoxide dehydrogenase (SOD), as well as enzymes involved in the production of eicosanoids, such as cyclooxygenase (COX) and lipoxygenase (LO). There is increased interest in the use of polyphenol-rich foods because of their immunomodulatory effect; however, the mechanisms used during macrophage responses are extremely complex and little is known about the effects of polyphenols on these cells. As such, this review summarizes the current view of polyphenol influences on macrophages.Keywords: polyphenols, inflammation, macrophage activation, cytokine modulation